Peningkatan Pendidikan Karakter Melalui Kegiatan Magrib Mengaji Bagi Anak Usia Sekolah di Desa Panongan Lor - Firmansyah, Bambang; Astriyani, Dina; Halimatussadiyah, Lidia; Rukmana, Teti; Hanifah, Ninif; Fakhriyah, Nisa (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Abstract Childhood and school-age years are a crucial period for character development, making it essential to be filled with values-based education. This community service initiative aims to support character education for school-aged children through the Magrib Mengaji (Qur’an recitation after sunset prayer) program. The method employed in this program is Participatory Action Research (PAR), emphasizing community-driven innovation by actively involving local figures in the process of change. The results of the program demonstrate that Magrib Mengaji meaningfully contributes to shaping children's character, particularly in fostering religiosity, discipline, and a sense of social responsibility. Positive behavioral changes were observed in various aspects. In terms of religiosity, children became more aware and consistent in performing the Maghrib and Isha prayers in congregation. In terms of discipline, they arrived before prayer time, showed orderliness during Qur’an recitation, and attentiveness during short sermons. As for social responsibility, it was reflected in how they communicated respectfully with teachers and peers, as well as how they maintained cleanliness and tidiness of the spaces and items they used.